Bharatiya Model of Governance: A Unique Blend of Traditional and Modern Systems - Dipikarani Lokare; Ashokkumar V. Paled, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
The Bharatiya model of Governance represents a unique harmonious blend of traditional Indian administrative wisdom and modern democratic principles deep-rooted in ancient texts from Vedic texts to the modern law of the land, i.e., Constitution. Traditional Governance emphasized on ethical Governance such as Dharma (Righteous Duty), Raj Dharma (Ethical leadership), Swadeshi (Self-reliance), Decentralised administration, and welfare-oriented state, whereas in contrast, Modern Governance shaped by Constitutional Democracy, Federalism, Global economic integration and Digital Transformation integrates these historical principles with contemporary Political, Economic and Technological Advancements. Despite its rich historical legacy and ongoing policy adaptations, it incorporates certain important elements while adapting to contemporary socio-political realities.This paper puts light on the Continuity and Transformation of Governance in India. Analysing how the ancient Governance ideals and its civilizational ethos relevance in modern Governance system to meet the Modern Governance Challenges, there remains a need for greater harmonization between tradition and modernity in policy making. Bharatiya governance highlights how India balances tradition with innovations on the technological advancement in Governance aligning with Ancient Governance enriching the Governance Framework that combines this Hybrid model of Governance with cultural values and global aspirations with adopting to best practices reaching its true potentialities.
Keywords: Democracy; Decentralised Administration; Digital Transformation; Federalism; Governance; Law